EFEKTIVITAS EKSTRAK BUAH LADA HITAM (PIPER NIGRUM L) KOMBINASI JAHE MERAH (ZINGIBER OFFICINALE) UNTUK MENGOBATI PENYAKIT VITILIGO - Mimatun Nasihah; Fajrin, Fitriana Ikhtiarinawati (2477 - 6165, 2019)
Vitiligo is a disease that causes skin color fading caused by cells that form melanin unfunctionally. The initial symptom is the appearance of white patches that will gradually become brighter and wider. Black pepper, aside from being used as a complement to cooking spices, its piperin content can stimulate the formation of skin melanin. Red Ginger is also believed to heal bad cells in the skin or restore damaged skin naturally, eliminating vitiligo because it contains collagen. This research used the experimental method. Data collection included pH test, organoleptic test, cream effectiveness test and pharmaceutical test. Data analysis used the Anova One Way to find out whether differences cream composition affected color, texture, thickness, and fondness. Test of T-Paired was used to determine differences vitiligo exposure before and after treatment. The comparison of Black Pepper: Red Ginger: Emulgade were (1:2:1), (1:1:1), (1:1:2), (1:1:3), and (1:3:8). Anova One Way test results showed that F-count to cream color (24,718)> F-table (4.53), F-count to cream texture (11,834)>F-table (4.53), F-count to cream density (15,001)>F-table (4.53) and F-count to cream fondness (6,517)>F-table (4.53). This showed that there was a significant difference for the combination of red ginger black pepper cream on color, texture, density and fondness on the cream. The effectiveness test of cream used T-paired test with result Tcount (5.277)>T-table (2.131), it showed that there was a significant difference in the vitiligo exposure before and after being given a cream of black pepper and red ginger. Pharmaceutical test explained that cream were homogeneous, semi-solid, had a distinctive odor, brownish yellow color, pH 6, and had a spread capacity of 5.2 cm.